Prognostic value of hypoxia-inducible factor-1 alpha in nasopharyngeal carcinoma: a meta-analysis. Issue 4 (November 2018) - Xie, Wenji; Liu, Lihui; He, Haixia; Yang, Kaixuan
Background: Over the past 5 years, many studies have reported the prognostic value of hypoxia-inducible factor-1 alpha (HIF-1α) in nasopharyngeal carcinoma. However, the results have not reached a consensus until now. Therefore, we performed this meta-analysis to investigate the influence of HIF-1α expression on the prognosis and clinical characteristics in nasopharyngeal carcinoma. Methods: We searched PubMed, the Cochrane Library, Embase (via Ovid interface), Web of Science, and China National Knowledge Infrastructure electronic databases from their establishment to 6 December 2017. We calculated the hazard ratio (HR) and the odds ratio (OR) to assess the prognostic and clinicopathological values of HIF-1α, respectively. Q test and I 2 statistic were applied to evaluate heterogeneity. We also conducted publication bias and sensitivity analyses. Results: A total of 18 studies with 1476 patients were included in our meta-analysis. We found HIF-1α expression was associated with poor overall survival (HR=1.77; 95% confidence interval (CI) 1.35, 2.32; P <0.001), poor progression-free survival (HR=1.72; 95% CI 1.22, 2.44; P =0.002), a higher rate of lymph node metastasis (OR=3.81; 95% CI 2.60, 5.58, P <0.001), and more advanced tumor stage (OR=2.98; 95% CI 1.79, 4.97; P <0.001). Conclusions: Our study demonstrated that HIF-1α could be an appropriate prognostic biomarker for nasopharyngeal carcinoma patients.